2020
DOI: 10.1016/j.toxrep.2020.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and antimicrobial potential of different leaves extracts of R. fruticosus used traditionally to treat diabetes

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…The BSLA results for the highly toxic plant extracts correlate with results from other toxicity studies. The toxicity result of Croton tiglium (Euphorbaceae), whose LC 50 = 1.32 μg/mL, is consistent with the anticancer activity exhibited by 12-O-tetradecanoylphorbol-13-acetate (TPA), a major active constituent of croton oil [ 201 ], although it is lower than the 30 μg/mL reported by Meyer et al in one of the pioneer studies using BSLA for active plant constituents [ 20 ]. The BSLA result of Arcangelesia flava , belonging to family Menispermeceae, is similar to the findings of Soonthornchareonnon and co-workers [ 202 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The BSLA results for the highly toxic plant extracts correlate with results from other toxicity studies. The toxicity result of Croton tiglium (Euphorbaceae), whose LC 50 = 1.32 μg/mL, is consistent with the anticancer activity exhibited by 12-O-tetradecanoylphorbol-13-acetate (TPA), a major active constituent of croton oil [ 201 ], although it is lower than the 30 μg/mL reported by Meyer et al in one of the pioneer studies using BSLA for active plant constituents [ 20 ]. The BSLA result of Arcangelesia flava , belonging to family Menispermeceae, is similar to the findings of Soonthornchareonnon and co-workers [ 202 ].…”
Section: Discussionsupporting
confidence: 62%
“…To assess the toxicity of the plants in parallel, we used the brine shrimp lethality assay (BSLA), which is a simple, reliable, inexpensive micro-scale bioassay technique that can detect a range of bioactivity in ethanolic extracts as well as isolated purified bioactive natural products [ 18 ]. This assay is based on the ability of the extract to kill laboratory-cultured brine shrimp nauplii, from the genus Artemia [ [19] , [20] , [21] ]. Brine shrimp lethality assay only requires small amounts of sample.…”
mentioning
confidence: 99%
“…Studies of the antimicrobial capacity of non-polar blackberry seed extracts are not reported in the literature. Weli et al [ 19 ] studied the antibacterial activity of blackberry leaf extracts (methanol, hexane, chloroform, ethyl acetate, and hydro-alcoholic) and concluded that they are effective against several Gram-positive and Gram-negative micro-organisms.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, given the high prevalence of chronic and erosive diseases, it necessitates using plants to provide the antioxidants needed by the body, especially plants that are high in phenol and flavonoids. Therefore, to provide the natural antioxidants needed by the body, the consumption of plants with high phenolic compounds is recommended (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%